Effectiveness of combined chloroquine and primaquine treatment in 14 days versus intermittent single dose regimen, in an open, non-randomized, clinical trial, to eliminate Plasmodium vivax in southern Mexico. (December 2015) - Gonzalez-Ceron, Lilia; Rodriguez, Mario; Sandoval, Marco; Santillan, Frida; Galindo-Virgen, Sonia; Betanzos, Angel; Rosales, Angel; Palomeque, Olga
Abstract Background In Mexico, combined chloroquine (CQ) and primaquine (PQ) treatment has been used since the late 1950s to treatPlasmodium vivax infections. Although malaria transmission has declined, current treatment strategies must be evaluated to advance towards malaria elimination. Methods The clinical and parasitological outcome of treating symptomaticP. vivax with the 14-day (T14) treatment or intermittent single dose (ISD) regimen was evaluated in southern Mexico between February 2008 and September 2010. Patients over 12 months old withP. vivax mono-infection and asexual parasitaemia ≥500 parasites/µl were treated under supervision. After diagnosis (day 0), treatment began immediately. T14 patients received CQ for 3 days (10, 10 and 5 mg/kg) and PQ daily for 14 days (0.25 mg/kg), while ISD patients received a single dose of CQ (10 mg/kg) and PQ (0.75 mg/kg) on days 0, 30, 60, 180, 210, and 240. Follow-up was done by observing clinical and laboratory (by microscopy, serology and PCR) outcome, considering two endpoints: primary blood infection clearance and clinical response at 28 days, and the incidence of recurrent blood infection during 12 months. Parasite genotypes of primary/recurrent blood infections were analysed. Results During the first 28 days, no differences in parasite clearance or clinical outcome were observed between T14 (86 patients) and ISD (67 patients). On day 3, 95 % of patients in both groups showed no blood parasites, and no recurrences were detected on days 7–28. Contrarily, the therapeutic effectiveness (absence of recurrent parasitaemia) was distinct for T14 versus ISD at 12 months: 83.7 versus 50 %, respectively (p = 0.000). Symptomatic and asymptomatic infections were recorded on days 31–352. Some parasite recurrences were detected by PCR and/or serological testing. Conclusions T14 was effective for opportune elimination of the primary blood infection and preventing relapse episodes. The first single dose of CQ-PQ eliminated primary blood infection as efficiently as the initial three-dose scheme of T14, but the ISD regimen should be abandoned. A single combined dose administered to symptomatic patients in remote areas while awaiting parasitological diagnosis may contribute to haltingP. vivax transmission. Alternatives for meeting the challenge of T14 supervision are discussed. Trial registration: NIH-USA, ClinicalTrial.gov Identifier: NCT02394197